Energy-efficient and water-saving sorbent regeneration at near room temperature for direct air capture. (March 2023) - Ji, T.; Zhai, H.; Wang, C.; Marin, C.M.; Wilfong, W.C.; Wang, Q.; Duan, Y.; Xia, R.; Jiao, F.; Soong, Y.; Shi, F.; Gray, M.
Abstract: This study reports energy-efficient and water-saving microwave-accelerated regeneration of sorbent (MARS) for dilute carbon capture from the ambient air. The experimental studies indicated that the CO2 desorption rate from the chemisorbents increased with microwave output under near-isothermal conditions at near room temperature . The reduced activation energy of MARS, i.e., 20–28 kJ/mol, indicated enhanced CO2 desorption kinetics by microwave-induced rotational–vibrational (rovibrational) coupling transitions, primarily due to the highly polarized feature of the carbamate (CO2 -PEI). The instant and selective delivery of microwave energy to the targeted polarized C–N bonds at room temperature is particularly advantageous for energy-efficient direct air capture. The experimental results also demonstrated a good working capacity of 0.6–1.4 mmol of CO2 /g and a promising rapid MARS-DAC process with microwave swing. As it does not require steam regeneration and heat exchanger, a simple MARS process is attractive for CO2 capture in water-stressed regions.